POLITENESS STRATEGIES OF THE COMMENTS TOWARD TRUMP'S INSTAGRAM POST ON 'INTERNATIONAL WOMEN’S DAY' - Yunisaa Ammaida (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2020)
The purpose of this study was  to describe politeness strategies employed by the users to give comment toward Donald Trump’s Instagram Post on International Women’s Day and to explain the factors that influence the users to use the strategies. The researcher used the theory of politeness strategy by Brown and Levinson (1987).  In this research, the researcher applied descriptive-qualitative method. Because this research is to more explain about the findings politeness strategies employed by the users to give comment toward Donald Trump’s Instagram post. The data were taken from comment/utterance and source of data use document such Donald Trump Instagram Post. The instrument of this research is the researcher herself. Technique of collecting data use documentation methode and technique of analysing data use data reduction, data display, and conclusion. Then, the researcher uses source triangulation to validate the data. The researcher asks lecturer who master in Linguistic as validator of source data trianggulation. In this reserach, the researcher found positive politenes strategy is the highest strategy with total 276 (53%) data out of 525 data used by the users to give the comment toward Donald Trump’s Instagram post on International Women’s Day. The researcher also found social distance factor which factor is mostly influence the users used politeness strategy. It means when the users use social media to give comment, they want to show solidarity, treat the other users as a member of in-group, a friend, a person who are known and liked. So it can save the users and Donald Trump’s face and can minimize the distance between the user and Donald Trump.